Ultrafine fully vulcanized natural rubber modified by graft-copolymerization with syrene and acrylonitrile monomers. Issue 1 (1st March 2022) - Longsiri, K; Mora, P; Jubsilp, C; Hemvichian, K; Rimdusit, S
Abstract: Natural rubber (NR) is known as one of the most important renewable agricultural resources in Thailand. To enhance the NR's value, development and utilization of NR in form of commercial product are necessary. Commercial product based on ultrafine fully vulcanized powdered rubber (UFPR) was widely used in numerous potential applications such as toughening filler or friction modifier in brake pads. However, to meet the required thermal stability of friction modifier in brake pads for replacing the synthetic rubber powder, the modification of NR by graft-copolymerization with styrene (ST) and acrylonitrile (AN) monomer and production into the powder form are promised related to a sustainable economic system. From the beginning, the grafting process of NR latex was prepared by emulsion graft-copolymerization with ST and AN monomers onto deproteinized natural rubber (DPNR). The results revealed that the grafting with ST/AN monomer content of 80/20 weight ratio possessed the monomer conversion and grafting efficiency as high as 71% and 63%, respectively. After that, the obtained DPNR-g-(PS-co-PAN) was radiated by an electron beam, followed by a spray drying process to produce ultrafine fully vulcanized powdered natural rubber (UFPNR-g-(PS-co-PAN)). The SEM micrographs showed that UFPNR particles are relatively spherical with a particle size of approximately 3.56 μm. Furthermore, thermal stability i.e., degradation temperature at 5 % weight loss (Td5) of the modified UFPNR was substantially improved from 334 to 350°C. The benefits of these advanced technologies give an obvious conclusion proved that the modified UFPNR is a good candidate for replacing a commercial synthetic powdered rubber and suitable for using as toughening filler in high performance polymer composite applications.